mathamethics
 👍 0
 👎 0
 👁 87

 👍 0
 👎 0
Respond to this Question
Similar Questions

Algebra
I'm not quite sure about these problems. I know how to do them, but it seems that I get the wrong answer. Maybe I'm supposed to get 'no solution' but I'm not sure. Could someone please help me with them? 565x=15x35
asked by Maria on September 14, 2006 
Maths
Test the solution of an equation: Prove that x=5 is a solution of the equation: 3x3=2x+2 LHS= RHS= LHS=RHS,ie x=5 is the solution.
asked by Dian on November 2, 2016 
mathamethics
RHS and LHS . 5p + 3 = 2p + 9
asked by Anonymous on August 29, 2012 
Math  Vectors
If "u = (2,2,1)", "v = (3,1,0)" and "w = (1,7,8)", verify that "u (dot) (v + w) = u (dot) v + u (dot) w". My work: LHS: u (dot) (v + w) = (2,2,1) (dot) (4,6,8) = [(2,2,1) (dot) (3,1,0)] + [(2,2,1) (dot) (1,7,8)] = [u (dot)
asked by Anonymous on February 26, 2008 
Math, Inequalities
Prove the following inequalities. Then state for which values the LHS equals RHS. 1) a^2 + b^2 ≥ 2(ab1) 2) Given a + b = 1, prove the inequality a^2 + b^2 ≥ 1/2 Please explain how you solved it. Thanks.
asked by Anne on May 24, 2017

Maths
Cos^2A/sinAcosecA+sinA=0 Prove lHS =RHS
asked by Sneha on June 3, 2019 
Math: Law of Vectors (Cross Product)
(au) × v + (bu) × v = [(a + b)u] × v u = ( x , y , z ) v = ( x₂, y₂,z₂) LHS: = (au) × v + (bu) × v = [ ay z₂ y₂az ,  (axz₂ x₂az) , axy₂ x₂ay ] + [ by z₂ y₂bz ,  (bxz₂ x₂bz) , bxy₂ x₂by ]
asked by Anonymous on March 4, 2008 
Maths
I have a summation formula for Fibonacci numbers. n (SUM)F(2i)=F(2n+1)1 i=0 When the i value is changed from zero, and is then subbed into F(2i)the equation will not work. (RHS wont = LHS) eg: i=2 n=3 3 (SUM)F(4)=F(7)1 i=2 I
asked by Tim on November 4, 2008 
Math
I need to make one graph showing changes in population for deer and wolves. I'm stuck because the deer scale would go by 500's. but the wolves are very small and would go by 2's! I have no idea how i can make my yaxis of my
asked by Josh on April 2, 2007 
Maths
(x squared +y squared +z squared) / 3 = (x/3+y/3+z/3) squared Prove that if LHS equals to RHS, then all x=y=z Thank you
asked by Jason on August 1, 2019
You can view more similar questions or ask a new question.